Improbable libraries a visual journey to the world's most unusual libraries - Johnson, Alex 1969- (The University of Chicago Press, 2015)
Beautifully illustrated with two hundred and fifty color photographs, Improbable Libraries offers a breathtaking tour of the places that bring us together and provide education, entertainment, culture, and so much more. From the rise of the egalitarian Little Free Library movement to the growth in luxury hotel libraries, the communal book revolution means you'll never be far from the perfect next read.